Chapter Between Kafka and Gogol'. 'De-territorialising' National Narrative(s) in Post-Soviet Ukrainian Literature in Russian - Puleri, Marco (Biblioteca di Studi Slavistici, 2017)
Between Kafka and Gogol'. This suggestive title reflects the path that will be undertaken in this paper, approaching the two authors as privileged interlocutors in order to analyze the specific artistic dimension of the newest category of writers that has emerged in Ukraine following the post-Soviet historical fracture. Through the lenses of the peculiar features characterizing Franz Kafka's and Nikolaj Gogol's literary experiences, we will be able to highlight the nuances characterizing the specific cultural positioning of contemporary Ukrainian literary production in Russian.